An open‐source framework for analyzing N‐electron dynamics. II. Hybrid density functional theory/configuration interaction methodology. Issue 28 (1st August 2017) - Hermann, Gunter; Pohl, Vincent; Tremblay, Jean Christophe
Abstract : In this contribution, we extend our framework for analyzing and visualizing correlated many‐electron dynamics to non‐variational, highly scalable electronic structure method. Specifically, an explicitly time‐dependent electronic wave packet is written as a linear combination of N ‐electron wave functions at the configuration interaction singles (CIS) level, which are obtained from a reference time‐dependent density functional theory (TDDFT) calculation. The procedure is implemented in the open‐source Python programdet CI@ORBKIT, which extends the capabilities of our recently published post‐processing toolbox (Hermann et al., J. Comput. Chem. 2016, 37, 1511). From the output of standard quantum chemistry packages using atom‐centered Gaussian‐type basis functions, the framework exploits the multideterminental structure of the hybrid TDDFT/CIS wave packet to compute fundamental one‐electron quantities such as difference electronic densities, transient electronic flux densities, and transition dipole moments. The hybrid scheme is benchmarked against wave function data for the laser‐driven state selective excitation in LiH. It is shown that all features of the electron dynamics are in good quantitative agreement with the higher‐level method provided a judicious choice of functional is made. Broadband excitation of a medium‐sized organic chromophore further demonstrates the scalability of the method. In addition, the time‐dependent flux densities unravel the mechanistic details of the simulated charge migration process at a glance. © 2017 Wiley Periodicals, Inc. Abstract : In this article, the authors introduce a highly scalable procedure to investigate and visualize many‐electron dynamics in strong laser fields. It is implemented in an open‐source Python framework which builds up a space of pseudo‐CI singles wave functions from a linear‐response TDDFT reference. Using these as a basis, their non‐variational hybrid method evaluates transition moments of one‐electron operators for explicitly time‐dependent electronic wave packets. To demonstrate its capabilities and scalability, they use the time‐dependent electronic flux density to unravel the mechanistic details of the simulated charge migration in a medium sized dye.